2017
DOI: 10.1073/pnas.1617933114
|View full text |Cite
|
Sign up to set email alerts
|

Morphological features of IFN-γ–stimulated mesenchymal stromal cells predict overall immunosuppressive capacity

Abstract: Human mesenchymal stromal cell (MSC) lines can vary significantly in their functional characteristics, and the effectiveness of MSCbased therapeutics may be realized by finding predictive features associated with MSC function. To identify features associated with immunosuppressive capacity in MSCs, we developed a robust in vitro assay that uses principal-component analysis to integrate multidimensional flow cytometry data into a single measurement of MSC-mediated inhibition of T-cell activation. We used this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
173
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(196 citation statements)
references
References 58 publications
22
173
1
Order By: Relevance
“…Considering that PBMC-derived IFNγ is a key cytokine leading to MSC licensing in vitro , we examined the output of a simplified assay stimulating MSCs with recombinant IFNγ as a substitute for SEB-activated PBMCs (Galipeau and Krampera, 2015; Klinker et al, 2017). We observed that both Crohn’s disease and GvHD MSCs responded to IFNγ and upregulated the expression of IDO, CXCL9, CXCL10, CXCL11, CIITA, TRAIL, ICAM-1, HLADR, CCL5, and CCL7 in a manner closely paralleling that of the response to PBMCs (Figures 5D and 5E).…”
Section: Resultsmentioning
confidence: 99%
“…Considering that PBMC-derived IFNγ is a key cytokine leading to MSC licensing in vitro , we examined the output of a simplified assay stimulating MSCs with recombinant IFNγ as a substitute for SEB-activated PBMCs (Galipeau and Krampera, 2015; Klinker et al, 2017). We observed that both Crohn’s disease and GvHD MSCs responded to IFNγ and upregulated the expression of IDO, CXCL9, CXCL10, CXCL11, CIITA, TRAIL, ICAM-1, HLADR, CCL5, and CCL7 in a manner closely paralleling that of the response to PBMCs (Figures 5D and 5E).…”
Section: Resultsmentioning
confidence: 99%
“…IFN‐γ at concentrations from 5 ng/ml up to 100 ng/ml has been used to induce hMSC immune polarization with most of studies using IFN‐γ at concentrations between 20 ng/ml and 50 ng/ml . In addition to immune modulation, the influence of IFN‐γ on hMSC proliferation , trilineage differentiation , migration , transcriptome profile , and secretion of angiogenic and other tropic factors has been extensively reported.…”
Section: Introductionmentioning
confidence: 99%
“…These studies actively modified cell shape by culturing the cells on a number of micropatterned surfaces, initiating differentiation or stimulating with IFNγ, which all induces morphological changes in the hBM‐MSCs. These changes could either be used to alter the differentiation outcome or predict the BM‐MSC biology . The novelty of the current study lays in the use of naive hBM‐MSC morphology.…”
Section: Discussionmentioning
confidence: 99%